(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background and Aims: Inadvertent perioperative hypothermia (IPH) is defined as a peri-operative core temperature of less than 36°C. IPH is known to increase the risk of blood loss, prolonged and altered drug effects, post-operative shivering, and adverse cardiac events. Pre-operative warming with forced air reduces post-induction redistribution hypothermia and prevents complications associated with hypothermia. The present study was conducted to compare the effect of preoperative forced-air warming on the incidence of perioperative hypothermia in patients undergoing general anaesthesia, who are pre-warmed versus those who are not pre-warmed.Material and methods: This randomized comparative prospective study was carried out on 170 adult persons of either sex, ASA (American Society of Anesthesiologists) physical status I -III scheduled for different surgeries under general anaesthesia who met eligibility criteria were randomly assigned either to group A in which pre-operative forced-air warming was done for 30 minutes or to group B in which pre-operative forced-air warming was not done. The incidence of hypothermia was compared between the two groups.Result: The incidence of hypothermia was significantly higher in the non-pre-warmed group as compared to the pre-warmed group. The incidence of postoperative shivering was significantly higher in the non-pre-warmed group. However, the incidence of an adverse cardiac event and increased blood loss was insignificant between the two groups.Conclusion-Based on observations and results of this study, the incidence of perioperative hypothermia was reduced in patients who were pre-warmed for 30 minutes before general anaesthesia in comparison to patients who were not pre-warmed.